PENDAMPINGAN KRITIK AL-QUR’AN DAN HADIS TENTANG FEOMENA IMAM PEREMPUAN PERSPEKTIF AMINA WADUD DI MAJLIS TA’LIM MUSLIMAT BEKASI - Nur Rofiah; Nurafni Bisinda; Aas Siti Sholichah; Ahkmad Shunhaji; Siti Nurkholilah (MADANI Abdimas : Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
Amina Wadud's thoughts are quite controversial regarding the permissibility of women being men's prayer leaders because for 1400 years, not a single cleric, either male or female cleric, dared to hold such an opinion, in fact Amina Wadud immediately put her opinion into practice by leading male and female prayers. so there was a lot of ridicule and insults aimed at him. From there, the question arises, why does Amina Wadud think that and what is behind it? The author conducted library research or qualitative library research to answer several of these questions. Data was collected from Amina Wadud's own writings, other writers' writings about her thoughts, and information from online media. From this information, the author first discusses the pros and cons of female prayer imams. Then continues with Amina Wadud's opinion, which is accompanied by the basis she uses to support her opinion. This study shows that Amina Wadud uses tafsir tauhid, a holistic interpretation method adopted by Fazlurrahman in interpreting the Koran and hadith. Because by applying this monotheistic interpretation, he believes that reading the Koran about women's rights is no longer based on gender, but can reveal important principles such as justice and equality, as shown by the Umm Warakah hadith